STRUCTURAL RELAXATION IN THE MNCO3-CACO3 SOLID SOLUTION: A MN K-EDGE EXAFS STUDY - Lee Y.J.; Reeder R.J.; Wenskus R.W.; Elzinga E.J. (My University, 2002)
Mn K-edge EXAFS spectroscopy of solid-solution samples encompassing the complete MnCO3-CaCO3 series shows that first-shell Mn-O distances deviate little from the 2.19-A distance observed in pure MnCO3. Very slight lengthening is observed only in the limiting case of dilute Mn(II) calcite solid solutions, where the Mn-O distance is 2.21 A. The observed nearly complete structural relaxation and the composition independence of the Mn-O distance are consistent with the Pauling model behavior of solid solutions, and agree with previous studies showing a high degree of relaxation around hetero-sized substituents in the calcite structure. Strain occurs through bond bending, which is facilitated by the exclusively corner-sharing topology of calcite. Observed distances from Mn to more distant neighbors show significant variation across the solid-solution series that resembles Vegard's law-type behavior but reflects averaging. The high degree of relaxation suggests modest enthalpies of mixing in the solution, consistent with calorimetric studies.
Keywords: CALCITE; RHODOCHROSITE; EXAFS; SOLID SOLUTIONS; RELAXATION; IMPURITIES